Educational Technology and Teacher-Student Technology Competency: a Pathway to Teaching English with Technology - Ismail Anas (Journal of English Language Teaching and Linguistics, 2019)
This article presents a pathway to teaching English with technology which focuses on the elaboration of three essential approaches; they are 1) the technology tools (TT), 2) the teacher technology competency (TTC), and 3) the student technology competency (STC). Although EFL teachers have wide access to the high-end technology tools, however, their application in instruction will not be successful without being supported by the teacher professional use and student acceptance of the technology. Preparing the EFL teachers for teaching English with technology requires a continuing evaluation regarding the readiness of the technology tools, TTC, and STC. These three approaches should be taken into account seriously to transform TEFL into technology in instruction. The implications for research, teachers, students, practice, curriculum developers, and EFL teacher educator will also be discussed.